Performance Analysis of Fast Closed-Loop Power Control For WCDMA Systems - Sim, Moh Lim (2003)
In this thesis project, the author has carried out a thorough study on the performance of an uplink wideband CDMA (WCDMA) cellular system under fast closed-loop power control. Two study approaches are taken. Firstly, analytical study is carried out over a simplified cellular system. A mathematical model for the received signal power is proposed in terms of the probability density function. A large number of important parameters affecting the system performance have been included. The parameters taken into account include Doppler frequency which is related to mobile station's velocity , number of resolvable multipaths , maximum allowable transmitted power, power control updating frequency , number of pilot symbols per transmission frame, and number of receive diversity antenna branches. A set of analytical expression is then derived for the evaluation of the system performance in terms of bit-error rate (BER). The proposed analytical analysis approach has been verified to give good prediction of the system BER performance through comparison with simulation. The mathematical expression derived allow quick analysis of how various parameters may effect the WCDMA system performance. Next, simulation approach is adopted where most of the assumptions made in the pervious analyses are relaxed. A number of parameters are not taken into account in analytical method, such as number of power control command bits, power adjustment step-size, feedback channel error rate, type of power estimator, and power adjustment step-size control logic due to mathematical complexity. With simulation approach, the study of these parameters can be carried out. The analytical expression derived earlier have helped to serve as a reference for calibrating the simulation program developed.